अनुसन्धानमा नवीनतम सूचना प्रविधिको प्रयोग - Bhandari, Mahendra (Haimaprabha, 2025)
The purpose of the current article is to identify the most cutting-edge information technology that has appeared in the field of study and research since the turn of the twentieth century. In this, an effort has been made to address issues relating to the most recent research provisions. In this, a qualitative framework based on the examination of documents has been used to implement an intentional sample selection approach. The study methodology itself has been made the theoretical underpinning of this paper. Here, the most recent technology linked to research design and publication are reviewed, as well as the most recent instruments for collecting and analyzing research material. The explosion of information technology, particularly computer and telecommunication technologies, have made it easier to gather, choose, classify, and analyze research resources, as has been discussed in this article. Additionally, it has been claimed that the most recent research methodologies that have been used provide adequate support for study papers, articles, and their verification. It has been determined that the use of information and communication technology has allowed researchers to overcome obstacles related to time, money, and technology in the field of study.